No Market of any Type - Murphy, John W. (Problemos, 2007)
[full article and keywords in English] The article deals on the significance of the market in the contemporary society. The author observes some moralizing position that the market as such promotes general alienation and increasingly developing fragmentation of the members of community. It is sustained the idea of Karl Marx that the individual at the standpoint of the market becomes the atom of the industrial forces and loses its own identity. The exploitative tendencies which Marx supplies that they increasingly intensify from the standpoint of the postcapitalistic society. The market is defined as self-dependent and autonomical deterministic entity which can be divorced from the usual array of social contingencies in the context of the social. The author affirms that it is stimulating not only social fragmentation and general alienation but it is inciting total irresponsibility which contradicts with the dogmas of Christianity, of christocentrism in the market-place and the philosophical notions of Emmanuel Levinas who follows these lead. The postindustrial forces manipulate by the individuals and reduce to the economical logical imperatives rendering them into the screws of reproductional apparatus just like the producible objects. So there are eliminated all the possibilities of social solidarity and establishes “unconscionable consumerism”. The author claims that in this particular case contemporary consumerism develops the deorganising forces in our society and takes us to the situation as Margaret Thatcher says, society does not exist at the marketplace.